Analysis of Users' Perception of Security and Trust in Information Security in the WhatsApp Chat Backup Feature - Mariska Diksy Yuniar; Rio Guntur Utomo (Politeknik Siber Cerdika Internasional, 2026)
Background: Advances in communication technology have driven the increased use of instant messaging apps like WhatsApp, including chat backup features, which are linked to security and user trust in cloud-based data storage. This situation is exacerbated by low user digital literacy, with most users unaware that WhatsApp message backups on Google Drive are not automatically protected by end-to-end encryption. Objective: This study aims to analyze the factors influencing user perceptions of security and trust in WhatsApp's chat backup feature and their impact on continued usage intentions using the Push–Pull–Mooring (PPM) model. Methods: Data were collected through an online questionnaire from 447 active WhatsApp users aged 20–50 in Indonesia and analyzed using Partial Least Squares Structural Equation Modeling (PLS-SEM) with the help of SmartPLS 4 software. Results: The results showed that institutional privacy concerns had no significant effect on usage intention (p = 0.123), while relative privacy protection had a significant but weak effect (p = 0.049; f² = 0.008). Regarding the mooring factor, evaluation cost (p < 0.001; β = 0.309) and transition cost (p < 0.001; β = 0.510) significantly influenced switching exhaustion, while replacement cost had no significant effect. Furthermore, switching exhaustion was shown to significantly influence usage intention (β = 0.418; p < 0.001). Conclusion: Results indicate that user decisions are influenced not only by perceived security and trustworthiness, but also by barriers and psychological fatigue when considering switching services. A Goodness of Fit (GoF) value of 0.460 indicates the model's overall performance is good.